RECYCLING OF PLUTONIUM ON MOLTEN SALT REACTOR TYPE FUJI-U3 - WULANDARI (NIM: 20215047), CICI
Molten Salt Reactor (MSR) has been selected as one of the Generation IV nuclear power system that was developed in Japan. The fuel salt is composed of 71.76% LiF, 16% BeF2, 12% ThF4 dan 0.24% 233UF4, and graphite as moderator. Specifically, we focused on Fuji-U3 design which is originally consider 233U/Th as main fuel and power thermal 450 MWth. In this study, we used reactor grade Plutonium, weapon grade Plutonium and super grade Plutonium. Neutronic calculation was performed by using PIJ and Citation modulo by SRAC 2002 code with JENDL 3.2 as data library. Based on the calculation, the criticality achieved by loading 2.68% of reactor grade Plutonium, 0.76% of weapon grade Plutonium and 0.60% of super grade Plutonium. The concentration of reactor grade Plutonium is higher than weapon grade Plutonium and super grade Plutonium. This is caused by the effective multiplication factor of reactor grade Plutonium is lower than weapon grade Plutonium and super grade Plutonium. And also, there is the fertile material in high concentration, it absorbed the neutrons in active core. Beside that, in this study we will analyzed another factor such as the conversion ratio and the neutron spectra from the reactor.